2007
DOI: 10.1143/jjap.46.1471
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Thin Native Oxide Layer on n-GaN by Electrochemical Process in Mixed Solution with Glycol and Water

Abstract: In this paper, we report on the feasibility of oxidizing n-GaN by an electrochemical process in a mixture containing an aqueous solution of tartaric acid and propylene glycol. Photons generated by UV illumination were supplied at the electrolyte-GaN interface during the oxidation process. In the constant-voltage mode, X-ray photoelectron spectroscopy analysis revealed that relatively thick Ga oxide layer formed on the n-GaN surface. However, the oxide surface was very rough. In addition, we found metallic Ga c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 12 publications
3
32
0
Order By: Relevance
“…5, for the untreated GaN surface, the Ga 3d spectrum can be decomposed into three components in addition to the Ga-N component (19.6 eV): those chemically shifted by 0.92 eV toward higher binding energy (BE), 0.49 toward lower BE, and 1.76 eV toward lower BE, which can be assigned to Ga bonding to oxygen (Ga-O; 20.5 eV) [21,22], Ga bonding to N-H (Ga-NH; 19.21 eV) [23], and metallic Ga (17.5-18.4 eV) [24]. It has been reported that a metallic Ga layer forms on a damaged GaN surface [25].…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…5, for the untreated GaN surface, the Ga 3d spectrum can be decomposed into three components in addition to the Ga-N component (19.6 eV): those chemically shifted by 0.92 eV toward higher binding energy (BE), 0.49 toward lower BE, and 1.76 eV toward lower BE, which can be assigned to Ga bonding to oxygen (Ga-O; 20.5 eV) [21,22], Ga bonding to N-H (Ga-NH; 19.21 eV) [23], and metallic Ga (17.5-18.4 eV) [24]. It has been reported that a metallic Ga layer forms on a damaged GaN surface [25].…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…[47,48] This has already been shown to provide better control over surface termination [49] and subsequent surface coverage. [50] As etching techniques require the formation and subsequent dissolution of oxides, the degree of environmental degradation within an aqueous environment should provide insight into the more reactive species on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…We have investigated the feasibility of wet oxidation technique with glycol solution for surface passivation of GaN-based devices [1]. The wet oxidation was performed in a mixture of propylene glycol and 3wt% tartaric acid, as shown in Fig.…”
Section: Electrochemical Oxidation Of Gan and Algan For Surface Passimentioning
confidence: 99%